Assessment of the apical seal of root canals using different filling techniques. - Leonardo, Marcela V; Goto, Edson H; Torres, Carlos R G; Borges, Alessandra B; Carvalho, Cláudio A T; Barcellos, Daphne C (Nihon University School of Dentistry, 2009)
The aim of this study was to investigate the apical leakage of roots filled by three different gutta-percha techniques: lateral condensation, Tagger's hybrid and E&Q Master. Forty-two extracted single-rooted teeth were used. The coronal part of each tooth was removed and the root received biomechanical preparation using a 60-K file. The roots were randomly divided into three groups according to the technique of filling the root canal: Group I, lateral condensation; Group II, Tagger's hybrid; Group III, E&Q Master. The roots were submitted to dye leakage test with Rhodamine B for 7 days, using vacuum during the initial 30 min. The teeth were sectioned longitudinally and the leakage was measured in a linear fashion from apex to crown. Statistical analysis indicated that lateral condensation and E&Q Master techniques showed lower leakage than Tagger's technique (P = 0.0016). However, statistically no difference was found between lateral condensation and E&Q Master system techniques.
Keywords: AH Plus; coloring agent; diagnostic agent; epoxy resin; gutta percha; root canal filling material; adolescent; adult; endodontics; human; incisor; methodology; tooth disease; tooth root; Adolescent; Adult; Coloring Agents; Dental Leakage; Epoxy Resins; Gutta-Percha; Humans; Incisor; Root Canal Filling Materials; Root Canal Obturation; Tooth Apex; Young Adult